Faktor Analisis Manajemen Sarana dan Prasarana Terhadap Kinerja Tenaga Pendidik (Survey pada Sekolah Menengah Pertama Negeri 1 Kota Cirebon) - Adie Irwan Kusumah (Universitas Peradaban, 2015)
Facilities and infrastructure is one part of the existing management in educational institutions that have a very important role to support the educational process, especially the learning process. Based on the fact, the management of facilities and infrastructure have not been optimally performed by the school in achieving its objectives as an educational institution. Management or management is an integral component and can not be separated from the educational process as a whole, without the management is not possible educational goals can be realized optimally, effective, and efficient. Of these problems, the author is interested in conducting research with the title of the factor analysis of facilities and infrastructure management on the performance of educators survey at Junior High School 1 (SMPN 1) Kota Cirebon. The samples are saturated samples (census) so that the sample size is still 42 respondents. The test results F value of 15,027 while the F table at df (0,05;5,36) is equal to 2,477; so that t > t table or 15,027 > 2,477. This means that there is simultaneously a means and infrastructure management influence on the performance of teachers at SMPN 1 Kota Cirebon, whereas the correlation coefficient of 0,822 and the value of coefficient of determination obtained amounted to 0,676 or 67,60%. This percentage variables influence Infrastructures Management on the performance of educators at 67,60%. While the remaining 32,40% influenced by other variables not examined in this study. Factors that have contributed to the variable infrastructure management is the planning, procurement and utilization while maintaining dimensions and supervision do not contribute to the performance of teachers at SMPN 1 Kota Cirebon.